Anoplasty for anatomical anal stenosis: systematic review of complications and recurrences. (31st July 2022) - Gallo, Gaetano; Picciariello, Arcangelo; Di Tanna, Gian Luca; Pelizzo, Patrizia; Altomare, Donato Francesco; Trompetto, Mario; Santoro, Giulio Aniello; Roviello, Franco; Felice, Carla; Grossi, Ugo
Abstract: Aim: The optimal surgical treatment for anatomical anal stenosis (AS) remains to be determined. The aim of this study was to determine the rates of complications and recurrence after anoplasty for anatomical AS and, wherever feasible, compare the outcomes for the various techniques. Method: A PROSPERO‐registered systematic review was reported following the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines. Medline, PubMed, Embase, Cochrane Library of Systematic Review, Scopus and Web of Science were searched for articles published up to May 2021. Studies that assessed the outcomes of anoplasty in adult patients with anatomical AS were selected. The primary outcomes were complications and recurrence. The methodological quality of studies was appraised using the Joanna Briggs Institute critical appraisal tools. Results: From the total of 2705 unique screened records, 151 were assessed for eligibility. Only 29 studies (two prospective) met the inclusion criteria, reporting data on 556 patients [mean age 53 (18–83) years, 46% female]. Previous history of surgery for haemorrhoidal disease accounted for three quarters of cases. A total of 14 types of anoplasty were found, with the Y–V flap being the most performed technique [27% of cases ( n = 149)]. Complications frequently occurred, with a pooled prevalence of 10.2% (95% CI 3.9%–24.1%) after Y–V flap and 11.5% (5.3%–23.0%) after rhomboid/diamond flap. Patients undergoing house flap achieved better results in terms of clinical improvement, satisfaction and quality of life compared with Y–V flap and rhomboid/diamond flap. When considering only studies with at least 12 months of follow‐up, the pooled prevalence of recurrence was 4.7% (2.2%–9.8%), with significantly higher rates observed in the prospective versus retrospective series [pooled prevalence 18.9% (11.5%–29.5%) vs. 3.6% (1.7–7.8%), respectively; p < 0.001]. Conclusion: Both complications and recurrence were significantly lower after house flap compared with rhomboid/diamond and Y–V flap. Better designed multicentre studies with longer follow‐up are needed to confirm these findings. PROSPERO registration number: CRD42021239493.